Germany : Financial Sector Assessment Program: Detailed Assessment of Observance on Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2011)
Insurance regulation and supervision is of a high standard, and most of the enhancements suggested have been put in place. Further enhancements will be required, in the context of the forthcoming introduction of Solvency II requirements, in such areas as the frequency of onsite inspections, the enhancement of resources, and stability analysis. The government acknowledges the need to continue to develop supervisory capacity. Most of the requirements and supervisory tools, which are in use for the supervision of primary insurers, are also applied to the reinsurers.